Cold Extraction of Phyllanthus Niruri, Chromolaena Oodorata, Melastoma Malabathricum & Azadirachta Indica Via High-Pressure Processing (HPP): Evaluation of Physiochemical Properties and Antioxidant Activity - Nurul Fatihah Ibrahim; Faiz Razali; Hariz Haikal Nasuha; Angzzas Sari Mohd Kassim; Sity Aishah Mansur; Aliff Hisham A Razak; Noor Akhmazillah Mohd Fauzi (Journal of Science and Technology, 2025)
Phyllanthus niruri, Chromolaena odorata, Melastoma malabathricum, and Azadirachta indica are among the many medicinal plants found worldwide. These plants have been widely used for medicinal purposes due to their rich bioactive compounds. Traditional extraction methods, such as boiling at high temperatures, can lead to the degradation of certain bioactive compounds, including phenolic compounds, which contribute to antioxidant activity. This degradation occurs due to heat-induced denaturation. As an alternative, High-Pressure Processing (HPP) was employed to minimize quality deterioration during extraction. HPP was conducted at two different pressures (200 MPa and 600 MPa) with three holding times (5, 10, and 15 minutes). For comparison, a traditional extraction method was also performed by boiling the samples at 100°C for 30 minutes. The extracts were analyzed for their physicochemical properties (pH and color), antioxidant activity, and total phenolic content (TPC). Antioxidant activity was assessed using the DPPH radical scavenging method, while TPC was determined using the Folin-Ciocalteu reagent. Among the tested samples, HPP-treated A. indica extract exhibited the highest antioxidant activity at 600 MPa for 10 minutes, achieving 88.55 ± 0.04% scavenging activity. The highest TPC was observed in HPP-treated A. indica at 200 MPa for 5 minutes. Based on the results, the optimal HPP parameters for maximizing antioxidant activity were found to be 600 MPa with a 10-minute holding time. In conclusion, HPP demonstrates significant potential as an effective extraction method for medicinal plant materials, offering a promising alternative to traditional heat-based extraction techniques. This study is novel in its comparative evaluation of multiple medicinal plant species under varying HPP conditions, providing new insights into parameter optimization for maximizing antioxidant yield.